2015
DOI: 10.1097/bpo.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Capsulolabral Reconstruction for Posterior Shoulder Instability in Patients 18 Years Old or Younger

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Following this index procedure, there was a recurrence rate of 69% (25 of 36 shoulders), which is considerably higher than in other patient subgroups. 1,11,21 Epileptics therefore appear to be prone to ongoing symptoms but exhibit a significantly lower rate of recurrence when treated with skeletal stabilization (P ¼ .004). Persistent postoperative seizures affected 82% (27 of 33 patients) of the cohort and are therefore likely to have been the principal factor contributing to this high recurrence rate.…”
Section: Discussionmentioning
confidence: 94%
“…Following this index procedure, there was a recurrence rate of 69% (25 of 36 shoulders), which is considerably higher than in other patient subgroups. 1,11,21 Epileptics therefore appear to be prone to ongoing symptoms but exhibit a significantly lower rate of recurrence when treated with skeletal stabilization (P ¼ .004). Persistent postoperative seizures affected 82% (27 of 33 patients) of the cohort and are therefore likely to have been the principal factor contributing to this high recurrence rate.…”
Section: Discussionmentioning
confidence: 94%
“…In our practice, after a failure of extensive nonoperative management or in the setting of recurrent dislocations, arthroscopic capsulorrhaphy and labral repair appear to comprise a reasonable and efficacious treatment, as supported by prior literature. 5,[7][8][9][10][11] Over 90% of patients in these studies returned to sport after this arthroscopic treatment, with recurrent instability rates between 5% and 8%. This first step is not apparently controversial and appears to be a well-accepted aspect of the treatment algorithm for posterior shoulder instability.…”
mentioning
confidence: 86%
“…Bradley et al (2013) reported the results of 200 consecutive shoulders in 183 athletes treated with arthroscopic capsuloabral reconstruction for unilateral posterior instability. Wooten et al (2014) retrospectively reviewed their results on 22 athletes (25 shoulders) aged 18 years or younger who underwent arthroscopic capsulolabral reconstruction for unidirectional posterior instability from 2002 to 2009. Contact athletes did not have any significant differences in outcomes when compared to the entire cohort.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…Recurrent posterior instability with arthroscopic posterior capsulolabral reconstruction has also been reported to be less than 10% (Wooten et al, 2014), with lower rates observed when suture anchors are used to address posterior labral-capsular pathology rather than using the intact chondrolabral interface in an all-suture labrocapsular reconstruction (Bradley et al, 2013).…”
Section: Complicationsmentioning
confidence: 99%